Perilaku Penggunaan Tas Belanja pada Ibu Rumah Tangga Tidak Bekerja dalam Perspektif Theory of Planned Behavior - Ludhini Volva; Djemdjem Djamaludin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
The usage of reusable shopping bag is one of pro-environmental behavior which needs to be encouraged to reduce plastic waste. This research aimed to analyze the influence of sample characteristic, attitude towards behavior, subjective norm, perceived behavioral control, and intention towards the usage behavior based on the theory of planned behavior. This research used cross-sectional design. The purposively selected locations were Cijujung Village and Panaragan Village which represent village and city area respectively. The sample in this research were 100 non-working housewives. The results showed that attitudes towards behavior, subjective norms, perceived behavioral control, and intention was in the moderate category. The result of regression test showed that the perceived behavioral control had a significant positive effect towards intention. The other result of regression test showed that the frequency of use is influenced positively by intention, subjective norms, and perceived behavioral control meanwhile it is affected negatively by the attitude towards behavior.